Comparison of mid-term clinical outcomes after treatment of ostial right coronary artery lesions with early and new generation drug-eluting stents: Insights from an international multicenter registry. (1st March 2018) - Mitomo, Satoru; Jabbour, Richard J.; Watanabe, Yusuke; Mangieri, Antonio; Ancona, Marco; Regazzoli, Damiano; Tanaka, Akihito; Nakajima, Akihiro; Naganuma, Toru; Giannini, Francesco; Latib, Azeem; Nakamura, Sunao; et al.
Abstract: Background: There are only a limited number of studies comparing clinical outcomes after treatment of right coronary artery (RCA) aorto-ostial (AO) lesions with early (E-) and new (N-) generation drug-eluting stents (DES). Methods: From January 2005 to December 2013, 334 de novo RCA AO lesions treated with DES (E-:142 lesions, N-:192 lesions) at 2 high-volume centers (Italy and Japan) were included in this study. The primary endpoint was target lesion failure (TLF) defined as composite of cardiac mortality, target vessel myocardial infarction, and target lesion revascularization (TLR). Results: Baseline and lesion characteristics were well balanced between the 2 groups. The size of the stents deployed (3.35 ± 0.37 mm vs 3.39 ± 0.33 mm, p = 0.29) and non-compliant balloons used for post-dilatation (3.55 ± 0.38 mm vs 3.62 ± 0.47 mm, p = 0.21) were similar between the two groups. The median follow-up period was 1432 (IQR: 703-2197) days in total population. The cumulative rate of TLF at 3 years was significantly higher in E-DES group when compared with N-DES group (37.7% vs 14.2%, p < 0.001), which was mainly driven by TLR (38.0% vs 11.0%, p < 0.001). Multivariable analysis revealed that N-DES [HR 0.22 (0.13–0.38), p < 0.001], stent underexpansion [HR 10.59 (6.23–17.97), p < 0.001], excessive aortic stent protrusion [HR 3.12 (1.87–5.23), p < 0.001], and proximal stent overlap [HR 1.74 (1.03–2.95), p = 0.03] were independent predictors of TLF. Conclusion: For the treatment of RCA AO lesions, N-DES were associated with a lower incidence of TLF at 3 years when compared with E-DES. N-DES use and suboptimal implantation characteristics were independent predictors of TLF.